Financial Inclusion and Rural Economic Resilience: Evidence from Indonesia’s Digital Payment Expansion - Setiawati, Ira (Moneta : Journal of Economics and Finance, 2024)
This study addresses the research gap on how digital financial inclusion, particularly through digital payment systems, shapes rural economic development in Indonesia. Despite rapid national growth of digital transactions, rural adoption lags significantly behind urban areas. The study aims to examine the extent to which digital payments influence rural GDP growth, household consumption, and economic resilience, especially in the post–COVID-19 period. The methodology employed a panel data regression framework with fixed effects and structural break analysis across 33 Indonesian provinces, supported by secondary data from national digital transaction trends, rural digital infrastructure, and post pandemic economic indicators. Supplementary qualitative insights were drawn from international case comparisons. The results show a strong positive correlation between digital payment adoption and regional GDP growth, particularly post 2020 reforms. Rural areas with improved digital infrastructure experienced enhanced financial participation, better household spending behavior, and increased micro enterprise productivity. However, persistent challenges such as limited digital literacy, infrastructural gaps, and regional inequalities hamper the full realization of digital financial benefits. The discussion situates these findings within global best practices (Kenya’s M-Pesa, India’s Digital India), showing that inclusive digital ecosystems require infrastructure, literacy, and regulatory coherence. The study advances the field by demonstrating how digital payment adoption can serve as a catalyst for rural resilience and inclusive development in emerging economies. In conclusion, digital financial inclusion represents a key lever for rural transformation in Indonesia. The integration of accessible, trusted, and scalable digital payment solutions into everyday economic life can promote inclusive growth and mitigate regional disparities.